2023
DOI: 10.1186/s12877-023-04064-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors influencing depression among empty nesters in China: A meta-analysis

Abstract: Background Empty nesters are older people who live alone or an older couple without children to care for them. In China, empty nesters make up a significant community and are more likely to experience emotional issues, particularly depression. This study investigated the prevalence of depression and the factors influencing depression among Chinese home-bound empty nesters using meta-analysis. Methods Based on previous studies, we used search terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These empty-nesters are more fragile to mental issues, especially depression because they have difficulty obtaining support from family. 66 , 67 One study showed that the overall prevalence of depression among Chinese empty-nesters was 43% in the 5337 samples. 66 Our study found that internet use significantly enhances the friend networks of Chinese older adults, and the mediating effect of friend networks is greater than that of family networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These empty-nesters are more fragile to mental issues, especially depression because they have difficulty obtaining support from family. 66 , 67 One study showed that the overall prevalence of depression among Chinese empty-nesters was 43% in the 5337 samples. 66 Our study found that internet use significantly enhances the friend networks of Chinese older adults, and the mediating effect of friend networks is greater than that of family networks.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 One study showed that the overall prevalence of depression among Chinese empty-nesters was 43% in the 5337 samples. 66 Our study found that internet use significantly enhances the friend networks of Chinese older adults, and the mediating effect of friend networks is greater than that of family networks. This finding, however, offers us an innovative perspective on combating depression in older adults in China.…”
Section: Discussionmentioning
confidence: 99%
“…With the transformation of the family life cycle, and the trend of independent living for children after marriage, the traditional family system’s position is weakened, more and more older adults people are becoming empty nesters ( 7 , 8 ). The “empty nester” refers to the older adults (over 65 years of age) who live alone or with spouse, because they have no children or their children are married or work outside for a long time ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that empty nesters are in a miserable situation in terms of quality of life [15], social support [16], and depression [17]. Does empty nesting lead to disability and cognitive impairment in the elderly?…”
Section: Introductionmentioning
confidence: 99%